Effect of anion type in the performance of ionic liquid/poly(vinylidene fluoride) electromechanical actuators - Mejri, R. (2016)
Low voltage actuators based on poly(vinylidene fluoride)(PVDF)with 10, 25 and 40 % 1-hexyl-3-methylimidazolium chloride ([C6mim][Cl])and 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C6mim][NTf2]) are prepared by solvent casting in order to evaluate the effect of anion size in the bending properties. Independently of the ionic liquid type and content, its presence leads to the crystallization of PVDF in the -phase. The addition of ionic liquid into the polymer matrix decreases significantly its degree of crystallinity and the elastic modulus. It is also confirmed the good miscibility between PVDF and IL,determinedby the interaction of the CF2groups from the PVDF chains with the imidazolium ring in the ionic liquid (IL). The AC conductivity of the composites depends both on the amount of ionic liquid content and anion size. The bending movement of the IL/PVDF composites is correlated to theirdegree of crystallinity, mechanical properties and ionic conductivity value and the best value of bending response (0.53 %) being found for IL/PVDF composite with40 wt% of [C6mim][Cl] at an applied voltage of 10 volts square signal.